The Effects of Process-Genre Approach on Academic Writing: Pengaruh Pendekatan Proses-Genre pada Penulisan Akademik - Alabere , Rabiat Ajoke; Shapii, Aspalila (JEES (Journal of English Educators Society), 2019)
This study intends to find out the effectiveness of Process-genre Approach (PGA) on academic writing in English as a second language Students' essay writing. The purpose of this paper is to determine how far this current global approach can be of benefit for the development of academic writing skills of the university students who are learning English as a second or foreign language. The participants were subjected to pre-test and post-test before and after intervention respectively. The experimental group was taught with the Process-genre approach while the control group was taught with the product (traditional) approach. The two groups went through 6 weeks of training with the differ- ent approach. The participants are university undergraduate students. The groups had 40 students for each. The data was analyzed by using analysis of Covariance (ANCOVA) to compare the scores of the experimental group with that of the control group. The findings of the study show that, the experimental group outperformed the control group proving that PGA is effective in teaching academic writing in tertiary institutions. The participants are homogeneous at the beginning of the intervention with no significant difference in the pre-test scores of the two groups while there is significant difference in the post test of the two groups. The PGA group scored higher than the PA group proving that there is an impressive performance of the students in academic essay writing of the PGA group of students. Therefore, PGA is an effective approach to teaching academic writing if properly applied.